The Influence of Microbial Community on Soybean Cyst Nematode Under the Condition of Suppressive Soil - Jie Song; Meiqi Liu; Qin Yao; Xiaoyu Zhang; Zhiming Zhang; Fengjuan Pan; Yanli Xu (Agronomy, 2025)
Disease-suppressive soils confer fitness advantages to plants after a disease outbreak due to the subsequent assembly of protective microbiota in natural environments. However, the role of ecological effects on the assemblage of a protective soil microbiome is largely elusive. In this study, we investigated the composition of parasitic microbes and their relationships with soybean cyst nematodes in suppressive soil. The results showed that parasitic microbial assembly along soybean cyst nematodes was shaped predominantly by the density of soybean cyst nematodes. We also found soybean continuous cropping increased the number of parasitic microbes of soybean cyst nematodes with the order of Ss > Sr > Sc, while it decreased the population of soybean cyst nematodes, resulting in a natural decline in the number of soybean cyst nematodes. These findings indicate that the population of soybean cyst nematodes accumulated parasitic microorganisms against this soil-borne disease under soybean long-term continuous cropping. Moreover, the metabolic activity of cyst parasitic microbes was increased by two years of continuous cropping (Sc) of soybean, and total carbon and total nitrogen of soil were the main impact factors in this short-term continuous cropping for metabolic patterns of the cyst parasitic microbes. In summary, the results highlight that the interaction of plants and disease shape the soil microbiome, recruit a group of disease resistance-inducing microbes, and modulate their beneficial traits to protect the plant.